In vitro maturation of oocytes is not associated with altered deoxyribonucleic acid methylation patterns in children from in vitro fertilization or intracytoplasmic sperm injection - Pliushch, Galyna; Schneider, Eberhard; Schneider, Tamara; El Hajj, Nady; Rösner, Sabine; Strowitzki, Thomas; Haaf, Thomas (Fertility and sterility, 2015)
Objective - To study the possible transmission, to the next generation, of epigenetic defects associated with in vitro maturation (IVM) of human oocytes. - Design - Case-control study using epigenetic data. - Setting - Two collaborating university departments. - Patient(s) - Eleven IVM newborns and 19 controls, conceived by conventional assisted reproduction. - Intervention(s) - Chorionic villus and cord-blood sampling. - Main Outcome Measure(s) - Using bisulfite pyrosequencing, we have measured average methylation levels of 6 imprinted (LIT1, MEG, MEST, NESPas, PEG3, and SNRPN), 5 tumor-suppressor (APC, ATM, BRCA1, RAD51C, and TP53), 2 pluripotency (NANOG and OCT4), and 2 metabolic (LEP and NR3C1) genes, as well as 2 repetitive elements (ALU and LINE1) in 2 tissues of IVM and control neonates. Using deep bisulfite sequencing, we have determined methylation patterns of many individual DNA molecules to detect rare RAD51C epimutations (allele methylation errors). - Result(s) - No statistically significant impact was found of IVM on chorionic villus and cord-blood DNA methylation at the studied developmentally important genes and interspersed repeats. The RAD51C epimutation rate was low (0.5% ± 0.1%) in all analyzed samples. - Conclusion(s) - IVM-induced epigenetic changes in offspring, if any, are relatively small in magnitude and/or infrequent.